PKM Membangun Literasi Siswa Sekolah Dasar Melalui Program Pembagian Buku Matematika Berbasis Kearifan Lokal di Wilayah Kota Ende : Pengabdian - Marselina Wali; Sesilia Olivia; Apriyani Soraya Ulfa; Alexius Ronal Pani; Fabianus Lengi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service Activity focuses on free book distribution activities that are collaborated with book introduction activities through interactive games. This activity aims to support the literacy program that has been launched in the school environment for 15 minutes before lessons begin so that students' literacy skills are better, so it is better to start from home because students have more time at home. The methods used in this activity are demonstration methods and participatory methods that can increase students' sense of ownership and responsibility for the process and results of the activity. This activity succeeded in increasing the interest in literacy and basic understanding of mathematics of elementary school students through the provision of educational books and interactive games based on local wisdom.